Sixth Workshop of the Agronomy Society of Nepal (ASoN) Theme: Agronomy for food security 10-11 March 2010 - Editor, The (Agronomy Journal of Nepal, 2013)
DOI: http://dx.doi.org/10.3126/ajn.v1i0.7553 Agronomy Journal of Nepal (Agron JN) Vol. 1: 2010 pp.134-140